Analysis of Solid Medical Waste Management at the Bengkuring Community Health Center UPTD Samarinda City - Junser Naibaho; Ilham Rahmatullah; Dewi Amon (Journal of Innovative and Creativity, 2025)
Community Health Centre is a health service provided by the local government for communities in both villages and cities. Government Regulation Number 18 of 2020 concerning Medical Waste Management in Regional Service Facilities. The Community Health Centre is a health service facility that has by-products of activities in the form of medical and non-medical waste. Therefore, the aim of this research is to analyse the medical waste management process at the Bengkuring Community Health Centre UPTD, Samarinda City. This type of research uses qualitative methods with a phenomenological approach. The informants in this study were the Head of the Community Health Centre, the Sanitarian, the Cleaning Service, and Patients, with a total of 4 informants.For data analysis techniques according to Miles and Huberman (Sugiyono, 2022). The results of this research show that in sorting, containing, and transporting solid medical waste in situ, there are still some things that do not comply with policies and SOPs. This research is expected to be a reference for UPTD Health Officers at Bengkuring Community Health Centre, Samarinda City, in the Solid Medical Waste Management Process so that they can create policies that are in accordance with operational standards and complete several facilities that still have procedural deficiencies.